Research landscape on 3D printing applications in healthcare within Southeast Asian countries: a systematic scoping review protocol - Wei Hong Lai; Muhammad Noorfaiz Mohd Noor; Mei Lian Leow; Yoon Khee Hon; Lee Len Tiong; Phei Ming Chern (BMJ Open)
Introduction Three-dimensional (3D) printing plays a significant role as a promising technological advancement in modern healthcare settings. 3D printing has been incorporated by many sectors worldwide including in Southeast Asian countries. However, there is a paucity of research, especially in the healthcare pertaining to 3D printing activity in the Southeast Asian region. Thus, a scoping review is conducted to gain insight into 3D printing healthcare research landscape in the Southeast Asian region.Methods and analysis The methodology draws on Arksey and O’Malley’s seminal framework for the scoping review. The literature search will be conducted by using keywords to find suitable published literature. The existing literature will be searched using selected electronic databases such as PubMed/MEDLINE, CINAHL, Scopus, ProQuest and Web of Science from the years 2011 and 2021. The selected publications will focus on 10 Southeast Asian countries: Malaysia, Indonesia, Singapore, Thailand, Brunei, Philippines, Laos, Vietnam, Cambodia and Myanmar. Two reviewers will be performing title and abstract screening for the criteria of each publication, in which they will be working independently of each other. The included publication will undergo a full-text review and references cited will be examined for relevance using the same inclusion criteria. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram will guide throughout the process. Data will be extracted, analysed and charted within each category from the selected publications for each Southeast Asian country.Ethics and dissemination The results of this scoping review will illustrate an overview of the 3D printing healthcare research in the Southeast Asian context, which can be a guide for the advancement of 3D printing that can be accentuated in future research. The results will undergo dissemination which will be submitted for publication in a scientific journal.